Association between coffee intake and gastroesophageal reflux disease: a meta-analysis. Issue 4 (1st June 2014) - Kim, J.; Oh, S.-W.; Myung, S.-K.; Kwon, H.; Lee, C.; Yun, J. M.; Lee, H. K.
Summary: Gastroesophageal reflux disease (GERD ) is one of the most common diseases affecting patients worldwide, but its risk factors and causes are not clearly known. The aim of this study was to investigate the effect of coffee intake on GERD by a meta-analysis. We searched online published research databases such as PubMed, EMBASE, and C ochrane L ibrary for studies that were published up to D ecember 2012. These publications were reviewed by two independent authors, and studies that fulfilled the criteria were selected. Whenever there was a disagreement between the authors, a consensus was reached by discussion. Fifteen case–control studies were included in the final analysis. A meta-analysis showed that there was no significant association between coffee intake and GERD . The odds ratio was 1.06 (95% confidence interval, 0.94–1.19). In subgroup analyses in which the groups were subdivided based on the definition of GERD (diagnosed by endoscopy or by symptoms alone), only the endoscopy group showed a significantly higher odds ratio. In subgroup analyses in which the groups were subdivided based on the amount of coffee intake, quality of study, and assessment of exposure, there was no significant association between coffee intake and GERD .